Prototype Sistem Kendali Pintu Gerbang Otomatis Berbasis Internet of Things (IoT): Indonesia - Anggreini, Novita Lestari; Ekawati, Nia; Ichsan, Hasbi Nur (Infotekmesin, 2023)
An automatic gate is a door whose operation process runs automatically using a remote drive tool, but when combined with IoT elements, it means that users can control the automatic gate using a cell phone or mobile phone. The purpose of this research is to create a prototype of an automatic gate control system based on the Internet of Things (IoT). The method used in the current research is the prototype method. The results in this study were tested to determine the range. Testing is done using an adapter connected to a power supply. The testing process is carried out by observing the movement and response of the servo motor when controlled via a smartphone and the stepper motor when the Ultrasonic sensor detects an object less than 5 cm. The conclusion of this research is that at a distance of 1 to 19 meters, the gate lock can still be controlled properly. While at a distance of 20 meters when the gate lock is open, the gate opens and closes. This is because the WiFi signal cannot be captured properly by the central controller of the circuit at a distance of more than 19 meters.